Astroglial alterations in the experimental spinal coro injury - Vaquero Crespo, J.; Oya, S.; Ramiro, M. J. (Investigación Clínica, 2013)
The authors studied the morphological changes that have been experimented by the astrocitary glia on the following eight days after a spinal cord traumatism in the rabbit. The results showed maximum alterations on the fourth day of the injury with infla mmatory cells and also very important structural changes_ In between the fourth and eighth day there appeared elements identified as astrocytoblasts and glioblasts with a possible phagocytosis mission. Later, far away in the zone of the spinal cord injury images of dead cells appeared, which affected the astroglial elements.